2012
DOI: 10.3329/bvet.v28i2.10677
|View full text |Cite
|
Sign up to set email alerts
|

Pathological study on the upper respiratory tract infection of chickens and isolation, identification of causal bacteria

Abstract: The proportional occurrence of bacteria and pathological lesions in the nasal sinuses and trachea of dead chickens were determined during [2008][2009]. Nasal sinus and tracheal swabs from 50 dead birds were collected in sterile nutrient broth. The histopathological samples were collected in 10% neutral buffered formalin and studied with light microscope. The isolation and identification of bacteria were performed by culture, staining and biochemical tests. The proportional occurrence of bacteria in trachea (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
(11 reference statements)
2
6
2
Order By: Relevance
“…7) was 8.69% ( 2 Klebsiella sp. in 23 isolates from 30 nasal passage swabs) in the present study which was higher than the values reported by Popy et al (2011) in Bangladesh. In that study the prevalence of Klebsiella sp.…”
Section: Colony Characters Staining Characters and Biochemical Testscontrasting
confidence: 56%
See 1 more Smart Citation
“…7) was 8.69% ( 2 Klebsiella sp. in 23 isolates from 30 nasal passage swabs) in the present study which was higher than the values reported by Popy et al (2011) in Bangladesh. In that study the prevalence of Klebsiella sp.…”
Section: Colony Characters Staining Characters and Biochemical Testscontrasting
confidence: 56%
“…Recent investigation (Popy et al, 2011) in Bangladesh showed that the prevalence of bacteria 6.03% Klebsiella sp., 38.79% Escherichia coli., 8.26% Pasteurella sp., 5.17% Bacillus sp., and 41.37% Staphylococcus sp., were present in both trachea (n=50) and nasal sinuses (n=50) of dead chickens.Thus, it is revealed that the bacteria of nasal passages of chickens cause a great loss to the farmers. So, the present investigation has been undertaken to enrich the knowledge of stockholders with a view (a) to isolate, identify and detect the prevalence of the bacteria from nasal passage of chickens and (b) to determine the pathological lesions in nasal passage.…”
Section: Ornithobacterium Rhinotracheale Has Recentlymentioning
confidence: 99%
“…(10.2%),Dashe et al (2013); (8.8%)Dashe et al(2008), N. Popy et al (2011, and are differed with the result received by Burtram C. Fielding et al(2010),Rajaa, et al (2011) who recorded higher isolation rate of Klebsiella pneumoniae (40.4), Botchris et al(2012): klebsiella isolated associated with bile and intestinal content of slaughtered chickens (63%) of samples. Also lower prevalence rate was recorded byHajieh (2008) resuts who isolated klebsiella form (1%) only of samples tested,Dashe et al (2008) detected klebsiella in (1.5%) of samples(Aher et al 2012) isolated klebsiella in (6.5%) of collected samples.…”
mentioning
confidence: 82%
“…Under field conditions, staphylococcus sp. are commonly recovered from chicken’s respiratory tract tissues with respiratory clinical symptoms, with a higher prevalence among other causative agents (50.2% as reported by Türkyilmaz [ 60 ] and 41.4% as reported by Popy, et al [ 61 ]).…”
Section: Avian Influenza and Other Bacterial Co-infectionsmentioning
confidence: 99%